'Aspect' as a feature of meaning in the Classical Greek verb. Issue 41 (2020) - Hazel, John
Abstract : This Journal published in 2016 an article by Jerome Moran on 'Tense, Time and Aspect in the Greek Verb' (Moran, 2016). It rightly pointed to the unsatisfactory nature of the treatment of the concept of 'verbal aspect' in available grammars and language courses, but did not sufficiently, I think, throw light on the issue for practising teachers and their students, nor did it satisfactorily clarify the intellectual issue posed. And yet this concept, which is not difficult to understand, is all-embracing and lies at the heart of the meaning of verbs in the classical language so that it is important to understand the distinctions it provides within the scope of the Greek verb.